2023
DOI: 10.3390/life13030752
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Ozone Therapy in Kidney Disease: A Review

Abstract: Ozone (O3) is a reactive oxygen species (ROS) that can interact with cellular components and cause oxidative stress. Following said logic, if O3 induces such a stressful milieu, how does it exert antioxidant functions? This is mediated by controlled toxicity produced by low concentrations of O3, which enhance the cell’s suppliance of antioxidant properties without causing any further damage. Therapeutic concentrations vary extensively, although 50 µg/mL is commonly used in experimental and clinical procedures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Lower dosages (50 or 100 mg/kg) or shorter periods (5 or 7 days) are almost without histochemical and biochemical consequences. It has been reported that the nephrotoxicity induced by GN involves different pathways, including oxidative stress (OS), inflammation, nitric oxide (NO) generation, lipid peroxidation, and decreased efficiency of kidney antioxidant enzymes such as superoxide dismutase (SOD), catalase, glutathione peroxidase, and reduced glutathione (GSH) levels [21]. This is in accordance with the results obtained in our study, which revealed that the GN-treated group had increased (OS) by depleting the activity of antioxidant enzymes and showing a drastic increase in ROS/RNS levels, leading to protein damage and increased levels of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Lower dosages (50 or 100 mg/kg) or shorter periods (5 or 7 days) are almost without histochemical and biochemical consequences. It has been reported that the nephrotoxicity induced by GN involves different pathways, including oxidative stress (OS), inflammation, nitric oxide (NO) generation, lipid peroxidation, and decreased efficiency of kidney antioxidant enzymes such as superoxide dismutase (SOD), catalase, glutathione peroxidase, and reduced glutathione (GSH) levels [21]. This is in accordance with the results obtained in our study, which revealed that the GN-treated group had increased (OS) by depleting the activity of antioxidant enzymes and showing a drastic increase in ROS/RNS levels, leading to protein damage and increased levels of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous studies have found a negative correlation between O 3 and the rate of decline in kidney function, this result needs to be interpreted with caution. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous studies have found a negative correlation between O 3 and the rate of decline in kidney function, this result needs to be interpreted with caution. [35] F I G U R E 2 Forest plot of the association between O 3 exposure and CKD risk. The size of the gray boxes for each point estimate represents the size of the included study.…”
Section: Principal Findingsmentioning
confidence: 99%
“…However, study on the effects of O 3 on the renal outcome and mortality in chronic kidney disease (CKD) is lacking. While it has been observed that there is a correlation between long-term exposure to O 3 and the prevalence of CKD, as well as an inverse correlation with eGFR [ 13 , 14 ], some experimental studies have reported that O 3 may play a role in the treatment of kidney disease [ 15 ]. Therefore, further research is needed to determine whether long-term exposure to O 3 affects the long-term prognosis of CKD.…”
Section: Introductionmentioning
confidence: 99%